PRELIMINARY PHYTOCHEMICAL SCREENING AND IN VITRO ANTIMICROBIAL ACTIVITY OF THE LEAF EXTRACT OF THUNBERGIA COCCINEA (FAMILY-ACANTHACEAE) - SULTANA, NARGIS; DAS, SUMIT (International Journal of Current Pharmaceutical Research, 2019)
Objective: To estimate the antimicrobial activity of the leaf extract of Thunbergia coccinea in association with phytochemical analysis. Methods: The extraction of the leaves of Thunbergia coccinea was done by using a various solvent like petroleum ether, chloroform and methanol. The phytochemical constitutes are investigated by using standard methods. Antimicrobial activity of leave extract was carried out against gram positive bacteria (Staphylococcus aureus) and one gram negative bacteria (Escherichia coli). The anti-fungal activity of the plant extract was evaluated on Candida albicans. The testing was done by using disc diffusion method. The zone of inhibition was compared with standard Amikacin for anti-bacterial activity and fluconazole for anti-fungal activity. Results: The present investigation shows the phytochemical analysis which revealed the presence of alkaloid, flavonoid, cardiac glycoside, saponin glycoside, tannin and phenolics. The antimicrobial activity of plant extract is showed significant result against all three of the test organism. Conclusion: The present study concluded that the leaf extract of Thunbergia coccinea contain various phytochemicals and possess promising antimicrobial activity when compared with the standards.